Assessment of Creative Thinking in Cultural Context in Junior High School Students: A Psychometric Validation Study - Dina Puji Lestari; Lathiful Anwar; Mochammad Hafiizh (Universitas Suryakancana, 2026)
Creativity is a key component of twenty-first century competencies and an essential element of mathematical problem solving. In Indonesia, the curriculum emphasizes creativity, yet valid and reliable instruments for assessing students’ creative mathematical thinking remain limited. This study aimed to design and validate a culturally contextualized mathematical creativity test that measures fluency, flexibility, and originality through open-ended problem-solving tasks. The instrument consisted of two contextualized items: (1) a task based on Gobak Sodor, a traditional Indonesian game, requiring students to design and analyze geometric field partitions; and (2) a task based on Tempe Sanan, a local food product, requiring innovative cutting designs and area calculations. Responses from 23 junior secondary students were scored on a 1–4 scale for each creativity dimension, resulting in six observed variables. Data were analyzed using Exploratory Factor Analysis (EFA) to identify the latent factor structure, followed by Confirmatory Factor Analysis (CFA) to test model fit. EFA indicated a two-factor solution, with fluency forming one distinct factor and flexibility-originality clustering as another. CFA confirmed the adequacy of this two-factor model, with good fit indices (χ²/df = 1.42, CFI = 0.972, TLI = 0.953, RMSEA = 0.061, SRMR = 0.045). Both factors demonstrated high reliability (α = 0.87 and α = 0.94). The findings provide strong evidence that mathematical creativity in this context is best represented by two dimensions: ideational fluency and structural creativity (flexibility–originality). The study contributes to the development of culturally responsive and psychometrically sound instruments for assessing creativity in mathematics education, aligning with the goals of the Indonesian curriculum.